Han Suyin : the little voice of decolonizing Asia - Cui, Feng (2021)
Rosalie Matilda Kwanghu Chou (September 12, 1916/17–November 2, 2012), better known by her pen name, Han Suyin, was born in Xinyang, in south-eastern Henan province, to a Chinese father and a Flemish mother. When she was five her family moved to Peking (modern-day Beijing), where she started formal schooling. Han studied in a local Chinese school before transferring to a Catholic school where she was educated in both French and English. At 14, she decided to pursue a career in medicine, and in 1933 she was admitted to Yenching University. Han soon left to study medicine at the Brussels Free University on the Boxer Indemnity Scholarship Program but her dreams of becoming a doctor were interrupted by the start of the Second Sino-Japanese War, which forced her to drop out of college and return to China. She met her first husband, Tang Pao Huang, a Chinese nationalist military officer, on the return voyage and the two married in Wuhan in 1938. The couple moved to Chongqing, Sichuan province, the new capital of the nationalist government, and Han subsequently trained as a midwife and worked in a maternity hospital run by the US Christian mission in Chengdu. Destination Chungking (1942), her first published work, written with the assistance of an American missionary doctor, Marian Manly, recounts her experiences during this period.